Preparation, Comparison and Characterization of Dual Drug (Promethazine& Oxymetazoline) Selective Electrode - Ali, Mutaz A (Al-Nahrain Journal of Science, 2018)
A dual drug ion selective electrode has been constructed for the first time, based on promethazine hydrochloride(PMH) and Oxymetazoline hydrochloride (OMH) using phosphotungstic acid as ionophoreand di-butyl phosphate (DBPH) as a plasticizer. The major objective is find a newpolyvinylcloride PVC matrix combination that allows two ions or drugs to be tested within the same membrane and accounted as a modification for Moody and Thomas theory. Many combinations have been tested but the most successful one was in electrode no. 2 with 1% of each active material. The resulting membrane gives a linear range (1x10-4-1x10-1) M with respect to (PMH) and (5x10-4-1x10-2) M with respect to (OMH). The slope for the linear range obtained was 57.68 and 56.64 mV/decade with a correlation coefficient 0.9995 and 0.9999 while the detection limit was 1x10-4 and 3x10-4 M for the (PMH) and (OMH), respectively. The obtained results were very reliable compared with the original results obtained for single drug ion selective electrode. The pH effect was studied using different concentrations of the two active materials, and the interferences were also studied using separated solution method in the presence of (Li+1, Na+1, K+1, Ca+2, Mg+2, Zn+2, Fe+3, Al+3, and Cr+3) as interfering ions, given a remarkable results. The constructed electrode has been also successfully applied in the determination of sample using direct method, standard addition (SA) method, multi standard addition (MSA) method and precipitation titration (PT) method.